Rasionalitas Islam dalam Perspektif Ekonomi: Antara Moralitas dan Efisiensi - Dini Zahratul Husna; Fitria Sifa Lestari; Nurul Aini Lubis (Economie: Jurnal Ilmu Ekonomi, 2026)
This study examines the application of Islamic rationality in contemporary economic practices, focusing on the interaction between efficiency and morality. The pressure to achieve high productivity often creates a dilemma between maximizing economic outcomes and adhering to ethical and justice principles. The findings indicate that applying Islamic rationality helps individuals and institutions reduce excessive consumption, balance personal interests with public welfare, and make economic decisions that are both productive and ethical. Islamic economic education also plays a crucial role in shaping moral awareness, enabling actors to integrate ethical values with efficiency in daily practices. However, challenges remain, such as the limited holistic implementation of Islamic rationality and the insufficient integration of efficiency, morality, and rationality in real-world practices. Overall, Islamic rationality holds significant potential as a practical framework for creating an economy that is productive, ethical, and sustainable when moral principles and efficiency are consistently applied.